Awareness and willingness towards organ donation / Mohd Fadzrul Azree Mohd Asri - Mohd Asri, Mohd Fadzrul Azree (2014)
Organ donation is the act of donating an organ by a person so that it can be transplanted by surgical procedure in the body of recipient. Organ donation can benefit the recipient largely by improving health, quality and span of life and even save from death or other critical conditions like paralysis. Any person above the age of 18 is eligible to become a donor. Even younger under 18 can donate but must with permission from parent or guardian. Most organs are only can be transplanted after the donor is dead but there are some organ that can be donated even when the donators is alive. By getting registered as a donor with some trust, they will get a donor card which makes them eligible for donation soon after their death. A single donor's body can save up to 50 people. Age is not a constraint, which means that people aged 70 or 80 also can become successful donors. Organs that can be donated include kidneys, heart, liver, pancreas, intestines, lungs, skin, bone, bone marrow and cornea. Organ donations usually occur for patients with kidney failure, heart disease and lung disease. For patients who need a kidney or a liver, a living donor's organ can be utilized, since human are already born with an extra kidney. However, if the patient needs a heart, lung, pancreas or cornea, the organ needs to come from a deceased donor. According The Health Ministry, the recorded number of registered of people who is willing to donate their organ in Malaysia until 31 August 2013 is 233, 573 people of 0.81% of country population. The total of Malaysia patients still waiting for organ transplantation until 31st August 2013 is 16,945 patients mostly had kidney problems. Overall, the number of patients requiring donated organs has overcome the number of donors.